Alphabet soup within a porphyrinoid cavity: synthesis of heterocarbaporphyrins with CNNO, CNOO, CNSO and CNSeO Cores from an oxacarbatripyrrin. Issue 65 (30th July 2018) - Smolczyk, Tyler J.; Lash, Timothy D.
Abstract : The first examples of porphyrin analogues with four different core atoms have been synthesized from an oxacarbatripyrrin intermediate. Abstract : The first examples of porphyrin analogues with four different core atoms have been synthesized from an oxacarbatripyrrin intermediate. Acid-catalyzed condensation of the tripyrrin analogue with pyrrole or furan dialdehydes gave 22-oxa- and 22, 23-dioxacarbaporphyrins, while reactions with furan, thiophene or selenophene dicarbinols afforded diphenyl dioxa-, oxathia- and oxaselenacarbaporphyrins.